Women as sexual objects and as weapon in armed conflict areas of México and Colombia and the role of media - Juárez Rodríguez, Javier (Historia y Comunicación Social, 2014)
The present article is the result of six years of documenting and interviewing hundreds of people involved in cases of violence against women in areas of armed conflict in México and Colombia. This document analyzes the systematic discrimination and violence directed towards girls and women living in these areas by focusing on settings that exemplify the impunity and permissiveness of the patriarchal system. In addition, the present work not only details the important role played by journalists and the media, but it also highlights the obstacles that they must overcome while attempting to investigate and expose this reality.